Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Understanding and predicting infection dynamics for an endangered amphibian using long-term surveys of wild and translocated frogs - Talisin T. Hammond; Adam R. Backlin; Elizabeth A. Gallegos; Debra M. Shier; Ronald R. Swaisgood; Robert N. Fisher (Biological Conservation, 2025)

Correction: Revisiting conservation units for the endangered mountain yellow-legged frog species complex (Rana muscosa, Rana sierrae) using multiple genomic methods - Allison Q. Byrne; Andrew P. Rothstein; Lydia L. Smith; Hannah Kania; Roland A. Knapp; Daniel M. Boiano; Cheryl J. Briggs; Adam R. Backlin; Robert N. Fisher; Erica Bree Rosenblum (Conservation Genetics, 2024)

Revisiting conservation units for the endangered mountain yellow-legged frog species complex (Rana muscosa, Rana sierrae) using multiple genomic methods - Allison Q. Byrne; Andrew P. Rothstein; Lydia L. Smith; Hannah Kania; Roland A. Knapp; Daniel M. Boiano; Cheryl J. Briggs; Adam R. Backlin; Robert N. Fisher; Erica Bree Rosenblum (Conservation Genetics, 2024)
Insights from conservation genomics have dramatically improved recovery plans for numerous endangered species. However, most taxa have yet to benefit from the full application of genomic technologies. The mountain yellow-legged frog species complex, Rana muscosa and Rana sierrae, inhabits the Sierra Nevada mountains and Transverse/Peninsular Ranges of California and Nevada. Both species have declined precipitously throughout their historical distributions. Conservation management plans outline extensive ongoing recovery efforts but are still based on the genetic structure determined primarily using a single mitochondrial sequence. Our study used two different sequencing strategies – amplicon sequencing and exome capture – to refine our understanding of the population genetics of these imperiled amphibians. We used buccal swabs, museum tissue samples, and archived skin swabs to genotype frog populations across their range. Using the amplicon sequencing and exome capture datasets separately and combined, we document five major genetic clusters. Notably, we found evidence supporting previous species boundaries within Kings Canyon National Park with some exceptions at individual sites. Though we see evidence of genetic clustering, especially in the R. muscosa clade, we also found evidence of some admixture across cluster boundaries in the R. sierrae clade, suggesting a stepping-stone model of population structure. We also find that the southern R. muscosa cluster had large runs of homozygosity and the lowest overall heterozygosity of any of the clusters, consistent with previous reports of marked declines in this area. Overall, our results clarify management unit designations across the range of an endangered species and highlight the importance of sampling the entire range of a species, even when collecting genome-scale data.

Genetic structure and historic demography of endangered unarmoured threespine stickleback at southern latitudes signals a potential new management approach - Rachel Turba; Jonathan Q. Richmond; Sorel Fitz‐Gibbon; Marco Morselli; Robert N. Fisher; Camm C. Swift; Gorgonio Ruiz‐Campos; Adam R. Backlin; Chris Dellith; David K. Jacobs (Molecular Ecology, 2022)
Habitat loss, flood control infrastructure, and drought have left most of southern California and northern Baja California's native freshwater fish near extinction, including the endangered unarmoured threespine stickleback ( Gasterosteus aculeatus williamsoni ). This subspecies, an unusual morph lacking the typical lateral bony plates of the G. aculeatus complex, occurs at arid southern latitudes in the eastern Pacific Ocean and survives in only three inland locations. Managers have lacked molecular data to answer basic questions about the ancestry and genetic distinctiveness of unarmoured populations. These data could be used to prioritize conservation efforts. We sampled G. aculeatus from 36 localities and used microsatellites and whole genome data to place unarmoured populations within the broader evolutionary context of G. aculeatus across southern California/northern Baja California. We identified three genetic groups with none consisting solely of unarmoured populations. Unlike G. aculeatus at northern latitudes, where Pleistocene glaciation has produced similar historical demographic profiles across populations, we found markedly different demographics depending on sampling location, with inland unarmoured populations showing steeper population declines and lower heterozygosity compared to low armoured populations in coastal lagoons. One exception involved the only high elevation population in the region, where the demography and alleles of unarmoured fish were similar to low armoured populations near the coast, exposing one of several cases of artificial translocation. Our results suggest that the current “management‐by‐phenotype” approach, based on lateral plates, is incidentally protecting the most imperilled populations; however, redirecting efforts toward evolutionary units, regardless of phenotype, may more effectively preserve adaptive potential.

Loss of dendritic connectivity in southern California's urban riverscape facilitates decline of an endemic freshwater fish - Jonathan Q. Richmond; Adam R. Backlin; Carey Galst‐Cavalcante; John W. O'Brien; Robert N. Fisher (Molecular Ecology, 2018)
Life history adaptations and spatial configuration of metapopulation networks allow certain species to persist in extreme fluctuating environments, yet long‐term stability within these systems relies on the maintenance of linkage habitat. Degradation of such linkages in urban riverscapes can disrupt this dynamic in aquatic species, leading to increased extinction debt in local populations experiencing environment‐related demographic flux. We used microsatellites and mtDNA to examine the effects of collapsed network structure in the endemic Santa Ana sucker Catostomus santaanae of southern California, a threatened species affected by natural flood–drought cycles, “boom‐and‐bust” demography, hybridization and presumed artificial transplantation. Our results show a predominance of drift‐mediated processes in shaping population structure and that reverse mechanisms for counterbalancing the genetic effects of these phenomena have dissipated with the collapse of dendritic connectivity. We use approximate Bayesian models to support two cases of artificial transplantation and provide evidence that one of the invaded systems better represents the historic processes that maintained genetic variation within watersheds than any remaining drainages where C. santaanae is considered native. We further show that a stable dry gap in the northern range is preventing genetic dilution of pure C. santaanae persisting upstream of a hybrid assemblage involving a non‐native sucker and that local accumulation of genetic variation in the same drainage is influenced by position within the network. This work has important implications for declining species that have historically relied on dendritic metapopulation networks to maintain source–sink dynamics in phasic environments, but no longer possess this capacity in urban‐converted landscapes.

Ephemeral stream reaches preserve the evolutionary and distributional history of threespine stickleback in the Santa Clara and Ventura River watersheds of southern California - Jonathan Q. Richmond; David K. Jacobs; Adam R. Backlin; Camm C. Swift; Chris Dellith; Robert N. Fisher (Conservation Genetics, 2015)